Effect of folic acid supplementation on risk of new‐onset diabetes in adults with hypertension in China: Findings from the China Stroke Primary Prevention Trial (CSPPT). (22nd January 2016) - Qin, Xianhui; Li, Jianping; Zhang, Yan; Chen, Dafang; Wang, Binyan; He, Mingli; Fu, Jia; Tang, Genfu; Cai, Yefeng; Shi, Xiuli; Xu, Xin; Hou, Fan Fan; et al.
Abstract: Background: The aim of the present post hoc analysis of the China Stroke Primary Prevention Trial (CSPPT) was to evaluate the effect of folic acid supplementation on the risk of new‐onset diabetes in hypertensive adults in China. Methods: In all, 20 702 hypertensive adults with no history of stroke and/or myocardial infarction (MI) were randomly assigned to receive double‐blind daily treatment with tablets containing either: (i) 10 mg enalapril and 0.8 mg folic acid (n = 10 348); or (ii) 10 mg enalapril alone (n = 10 354). New‐onset diabetes was defined as either self‐reported physician‐diagnosed diabetes or the use of glucose‐lowering drugs during the follow‐up period of the CSPPT. Results: Over a median treatment duration of 4.5 years, new‐onset diabetes occurred in 198 (2.0%) and 214 (2.1%) subjects in the enalapril–folic acid and enalapril groups, respectively (hazard ratio [HR] 0.92; 95% confidence interval [CI] 0.76–1.12). Similar results were observed when analyses were limited to subjects with baseline fasting glucose (FG) <7.0 mmol/L (HR 0.85; 95% CI 0.62–1.14). Furthermore, there was no significant group difference in: (i) the risk of new‐onset FG ≥7.0 mmol/L (defined as FG <7.0 at baseline and ≥7.0 mmol/L at the last visit; relative risk [RR] 1.07; 95% CI 0.96–1.20); or (ii) the composite of new‐onset diabetes or new‐onset FG ≥7.0 mmol/L (RR = 1.06; 95% CI 0.95–1.19). Conclusions: Among adults with hypertension with no history of stroke and/or MI in China, folic acid supplementation had no significant effect on the risk of new‐onset diabetes.